Bi2Te(IO3)O5Cl: a novel polar iodate oxychloride exhibiting a second-order nonlinear optical response1. Issue 5 (7th February 2015) - Geng, Lei; Meng, Changyu; Lu, Hongyan; Luo, Zhongzhen; Lin, Chensheng; Cheng, Wendan
<x xml:space="preserve">Abstract</x> A novel iodate oxychloride Bi2Te(IO3)O5Cl with a second-order nonlinear optical response originating from constructive stacking of dipole moments of IO3.